How the ongoing armed conflict between Russia and Ukraine can affect the global wheat food security? - Mottaleb, Khondoker Abdul; Govindan, Velu (Frontiers in Food Science and Technology, 2023)
This study explores the potential impacts of Ukraine-Russia war on wheat exports and global wheat food security. In the process, this study relies on wheat production, export, and consumption data from the Food and Agriculture Organization of the United Nations (FAO) and the United States Department of Agriculture (USDA), along with United Nations commodity trade data. At present Russia’s share of global wheat exports is nearly 16% and that of Ukraine nearly 10%. In 2020, at least 105 countries imported wheat from Russia and Ukraine. The sea ports in the Black Sea are major gateway of Russian and Ukrainian wheat to the world. These ports are almost unusable due to the armed conflict between Russia and Ukraine. The export restrictions on Russian and Ukrainian wheat have generated a supply shock, which has triggered wheat price in the international market. An ex-ante impact assessment of the present study suggests that the absence of wheat exports from Russia and Ukraine would reduce globally per capita daily energy and protein intake from wheat by 34%. Several countries in Asia and Africa rely on wheat imports from Russia and Ukraine to meet food demand, where food security and nutrition situation is already precarious. To avoid a potential crisis, this study suggests firstly wheat cultivation extensification and intensification in the countries, where there is a potential. In particular, closing the wheat yield gap in Africa and expansion of wheat area in South America, East Asia and Sub-Saharan African countries can significantly contribute to achieve food and nutrition security challenges in the globe.